IMPLEMENTATION OF FULL COST RECOVERY AND PERFORMANCE BASED REMUNERATION PERUMDA AIR MINUM TIRTA AMPERA BOYOLALI - Asmono, Insan Adi; Wuryanto, Y. Agung Tri Sulisto; Muhrom Ali; Novianto, Johan (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The implementation of Full Cost Recovery and Performance-Based Remuneration at Perumda Tirta Ampera Boyolali is a real step and best practice in BUMD Drinking Water governance. Tariff adjustments and governance reforms, especially performance-based remuneration, with static performance incentive patterns and dynamic incentives, performance deduction factors, individual performance and group performance and measurement of achievements or performance results. Performance-based remuneration is also followed by an Efficiency Work policy that is expected to reduce water loss (NonRevenue Water/NRW). The results of the tariff adjustment and performance-based remuneration have been positive. Based on 2002 and 2003 performance, there was an increase in performance from 3.12 to 3.39 contributed by service aspects, reduced water loss, increased customer connection water pressure, increased water meter replacement and human resource training. This policy has an impact on a significant increase in local revenue of Rp.493,137,143.50 fulfillment of employee rights which previously the company paid welfare benefits (50%) in 2022, in 2023 it can fulfill 100% welfare benefits, year-end incentives, incentives for Eid al-Fitr and Christmas.